Kebijakan Pemerintah Indonesia Mengatasi Problematika Dalam Dunia Pendidikan: Analisa Efektivitas Dan Rekomendasi Kebijakan - Alexandra, Frisca (Interdependence Journal of International Studies, 2020)
The education world in Indonesia still leaves a series of problems. There are still number of children in Indonesia whose having difficulty accessing education, the number of children dropping out of school still high, infrastructure disparities, teacher welfare issues and the quality of education in Indonesia that is still uneven have become homework for the Indonesian government. The government has made various efforts to fulfill the rights of Indonesian children to have education through the 9 year compulsory education program, which in 2015 the program was revised to 12 years. In addition, the government also provided education funding assistance through various policy programs from Bantuan Operasional Sekolah (BOS) in the era of President Susilo Bambang Yudhoyono to the Program Indonesia Pintar (PIP) in the era of President Joko Widodo. The budget for education sector in Indonesia also continues to increase every year, but this various government efforts has in fact not been effective enough to overcoming problems in education world. There are series of policy recommendations offered by the author such as improving the use of budget allocations to simplify the process of appointing honorary teachers who have been certified as teachers with PNS status. This set of policy recommendations is hoped to be an alternative solution for the Indonesia government in overcoming the problems in education world.